Religion in postsoviet Armenia: Pluralism and identity formation in transition - Sarkissian, Ani (Religion, state & society, 2008)
This paper examines the role of religion in identity formation and political development in postsoviet Armenia. It argues that the equation of Armenian identity with membership in the Armenian Apostolic Church contributes to an atmosphere of intolerance toward ethnic and religious minorities and inhibits the development of pluralism. This underdevelopment of a democratic culture therefore leads to weak opposition movements and delayed democratic consolidation. This paper is based primarily on interviews conducted in Armenia in 2005 with individuals in the religious and civil society sectors, but also draws upon evidence from published materials which demonstrate attitudes toward minorities in Armenian society.